Ribosome inactivation by Escherichia coli GTPase RsgA inhibits T4 phage - Fernández-García, Laura; Tomás, María; Wood, Thomas K. (Frontiers in Microbiology, 2023)
Introduction Bacteria must combat phages, and myriad bacterial anti-phage systems have been discovered that reduce host metabolism, for example, by depleting energetic compounds like ATP and NAD+. Hence, these systems indirectly inhibit protein production. Surprisingly, direct reduction of ribosome activity has not been demonstrated to thwart phage. Methods Here, by producing each of the 4,287 Escherichia coli proteins and selecting for anti-phage activity that leads to enhanced growth, we investigated the role of host proteins in phage inhibition. Results and discussion We identified that E. coli GTPase RsgA inhibits lytic phage T4 by inactivating ribosomes.